Internal and external load measures as predictors of overuse injury risk in professional football players - Varekamp, Charlene Ghislaine (Department of Health and Rehabilitation Sciences, 2019)
Background Football is the most popular sport worldwide. Football has grown into a faster, intensive and more competitive game with a substantial increase in technical and physical demands. To reach the peak demands of match play, extensive training is necessary to improve performance and to reach the top level in professional football. Inadequate training loads prevent optimal performance adaptions, place the player at higher risk of being underprepared and may increase the risk of overuse injuries. Determining an optimal training load that improves performance and decreases the risk of overuse injuries is important. Therefore, monitoring and understanding individual responses to training loads are necessary. To date there is limited research regarding prediction of risk of overuse injuries with respect to optimal TL in professional football players. Aim To describe the pattern of injuries and determine the influence of load metrics and injury risk in South African professional football. The total GPS distance covered, the number of GPS measured high-intensity sprints and session Rating Perceived Exertion load and the effects on the risk of developing an overuse injury in professional football players. Objectives (1) To determine the relationship between total GPS distance (m) covered, ACWLR and overuse injuries in a full competitive season. (2) To determine the relationship between GPS measured high-intensity sprints, ACWLR and overuse injuries in a full competitive season. (3) To determine the relationship between session rating of perceived exertion, ACWLR and overuse injuries in a full competitive season. (4) To determine the overuse injury risk per playing position (defenders, midfielders and attackers). (5) To determine the patterns of injury during a full competitive season. (6) To determine the effect of the internal load (sRPE) and external load (GPS) in a congestion week compared to a normal week on overuse injury risk. Methods Data was collected from 32 professional football players in the first and reserve team over one full competitive Premier Soccer League season (2016/17). Training load metrics were assessed using the acute:chronic workload ratio (ACWLR) to predict overuse injury risk within the team. The relationship between total GPS distance (m) covered (TDC), GPS measured high-intensity sprints (HIS), session rating of perceived exertion (sRPE) and ACWLR and overuse injuries was determined. Overuse injuries were described based on frequency, anatomical position and injury type as well as with regards to playing position (defenders, midfielders and attackers). The effect of a congestion week on overuse injury risk was also determined. Results No significant outcomes were recorded when predicting overuse injuries for the whole team, with regards to average TDC, HIS and sRPE ACWLR. Overuse injuries may be predicted when monitoring the individual player loads, thereby taking into account the peak demands of match play per playing position. Large difference between TDC and HIS and large increases or decreases (20%) within weeks may increase the risk of overuse injuries. Hamstrings and groins injuries are the most common injuries sustained and defenders sustained the most overuse injuries within the team relative to exposure time. Congestion weeks did not predict overuse injury risk.